Pengembangan Media Pembelajaran Berbasis Android Kodular dan Wordwall untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMP - Alizah, Laila; Agustina, Lady; Galatea, Chusnul Khotimah (Papanda, 2025)
The purpose of this research is to find out whether learning media based on android kodular and wordwall has an effect in improving students' understanding in solving math problems. The fundamental problems faced include the use of learning media still using the lecture method, the lack of interesting learning media in junior high schools, and students still have difficulty in solving problems. The research used is ADDIE which consists of five stages, namely: 1) Analysis; 2) Design; 3) Development; 4) Implementation; and 5) Evaluation. The test subjects in this development research were students of class VIII A SMPN 2 Tegalsari which is one of the schools in Banyuwangi Regency totaling 29 students. The results showed that the learning process using android-based learning media codular and wordwall had a major influence on improving students' mathematical problem solving. This can be seen in the validation results obtained validity of learning media with a score of 97.06% with the criteria “very valid”. Based on the results of the student response questionnaire with a total of 24 students who assessed the practicality of learning media obtained a score of 87.8% with the criteria “very practical”. In addition, based on the results of improving students' mathematical problem solving skills, during the pretest, 29 students obtained an average score of 35.1, while in the posttest an average score of 35.1 was obtained. This shows that the use of learning media based on android kodular and wordwall is effective in improving students' mathematical problem solving skills